Analisis Keamanan Pangan Segar Asal Tumbuhan (PSAT) Komoditas Beras Di Kabupaten Sukabumi - Widjayanti, Widjayanti; Akil, Syahrir; Jumiono, Aji; Widowati, Sri (Jurnal Ilmiah Pangan Halal, 2025)
This research aims to evaluate the safety level of rice in Sukabumi Regency in terms of heavy metal content and how to eliminate or minimize contamination until it’s safe to consume in accordance with Minister of Agriculture Regulation No. 53 of 2018 concerning the safety and quality of fresh food of plant origin. The research results showed that rice was safe from heavy metal contamination (cadmium, lead and arsenic), where cadmium was 0.05 – 0.13 mg/kg, arsenic was 0.13 mg/kg and lead was not detected. The maximum contamination limit (BMC) for cadmium is 0.4 mg/kg, lead is 0.2 mg/kg and arsenic is 0.3 mg/kg). So the heavy metal content is still below the maximum pollution limit (BMC). The washing stage can minimize the heavy metal content in rice, where washing rice once can remove the cadmium content from 0.07 mg/kg to undetectable. Cooking process can reduce the heavy metal content in rice. Washing once quite effective in removing heavy metals and cooking using rice cooker is more effective in maintaining the nutritional composition of rice compared to using steamer. The preparation of HACPP for rice production shows that the CCP is the process stages of receiving raw materials, fumigation and packaging.